2022
DOI: 10.3390/nu14183768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genistein on Common Kidney Diseases

Abstract: Genistein is a naturally occurring phytoestrogen (soy or soybean products) that is classified as an isoflavone, and its structure is similar to that of endogenous estrogens; therefore, genistein can exert an estrogen-like effect via estrogen receptors. Additionally, genistein is a tyrosine kinase inhibitor, which enables it to block abnormal cell growth and proliferation signals through the inhibition of tyrosine kinase. Genistein is also an angiogenesis inhibitor and an antioxidant. Genistein has effects on k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 215 publications
(218 reference statements)
0
5
0
Order By: Relevance
“…However, there is growing evidence of GEN’s potential benefits in other diseases and disorders. Studies have shown its neuroprotective [ 9 ] and nephroprotective [ 10 ] effect. It may have a positive impact on some parameters associated with increased risk of cardiovascular disease [ 11 ] and modulate genes involved in the inflammatory process, thus being potentially beneficial in the control of psoriasis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence of GEN’s potential benefits in other diseases and disorders. Studies have shown its neuroprotective [ 9 ] and nephroprotective [ 10 ] effect. It may have a positive impact on some parameters associated with increased risk of cardiovascular disease [ 11 ] and modulate genes involved in the inflammatory process, thus being potentially beneficial in the control of psoriasis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is a pleiotropic mediator of numerous proinflammatory cytokines that are activated via many stimuli including diabetic stress [ 193 ]. Collectively, these findings suggest that genistein suppresses the activation of NF-κB in various cell types under stress conditions, which is further indicating that the capacity of genistein to decrease the albumin-induced TNF-α release might be owing to the activation of NF-κB [ 160 , 194 , 195 ].…”
Section: Therapeutic Potential Of Anti-inflammatory Bioactive Agents ...mentioning
confidence: 97%
“…Specifically, it has been shown that genistein can inhibit the stimulation of the glutamine fructose-6-phosphate amidotransferase (GFAT) promoter. GFAT is a key enzyme in the HBP that catalyzes the conversion of fructose-6phosphate to glucosamine-6-phosphate [7]. Soy compounds may have anti-glycation properties, reducing the formation of advanced glycation end products (AGEs) associated with complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Soy compounds may have anti-glycation properties, reducing the formation of advanced glycation end products (AGEs) associated with complications of diabetes. Genistein can inhibit AGE-RAGE (receptor advanced glycation end products) binding, potentially reducing the downstream effects of RAGE activation [7]. Soy bioactives may influence the insulin signaling pathway in several ways.…”
Section: Introductionmentioning
confidence: 99%